2016
DOI: 10.3138/cpp.2016-035
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Impact of Population Aging on the Quebec Labour Market

Abstract: Quebecers are living longer than ever before as a result of better health as well as improved educational attainment and economic well-being. Using a dynamic microsimulation model, we show that an aging workforce will not necessarily mean a decline in Quebec employment levels in the coming years. Because future experienced workers will be more educated and more of them will remain in employment for longer, we project that annual growth rates in employment will stay positive, averaging between 0.2 and 0.3 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
0
0
1
Order By: Relevance
“…In addition, Schirle's study also found that population aging would lead to a decline in labor market participation rates, particularly among older workers. The author suggested that the government adopt policies that promote the older workers and maintain a balance taxation between and the provision of social benefits, such as pensions [9]. Schirle examined the impact of population aging on labor market participation rates in Canada and found that population aging would lead to a decline in labor market participation rates, particularly among older workers.…”
Section: Related Researchmentioning
confidence: 99%
“…In addition, Schirle's study also found that population aging would lead to a decline in labor market participation rates, particularly among older workers. The author suggested that the government adopt policies that promote the older workers and maintain a balance taxation between and the provision of social benefits, such as pensions [9]. Schirle examined the impact of population aging on labor market participation rates in Canada and found that population aging would lead to a decline in labor market participation rates, particularly among older workers.…”
Section: Related Researchmentioning
confidence: 99%
“…Výsledky potvrzují závěry předchozích výzkumů, že zdraví má významný pozitivní efekt na participaci mužů i žen na trhu práce. Bissonnette et al (2016) dochází k obdobným závěrům na příkladu 7 milionů obyvatel kanadské provincie Quebec. Posílení fyzického a mentálního zdraví jedinců fi guruje jako jedno z doporučení pro Českou republiku ve studii OECD (2017), a to na základě analýzy z let 2007-2017.…”
Section: Stav Zdravíunclassified